The factors influencing municipal solid waste generation in bauchi town, Nigeria - Harir, Adamu Isa; Gana, Bukar Abba; Kasim, Rozilah; Salihu, B. H (American Scientific Publishers, 2017)
This study investigated the factors influencing municipal solid waste generation (MSWG) in Bauchi town, the administrative headquarters of Bauchi state, Nigeria. The study used quantitative method, while experiments and questionnaire surveys, were used as the major instruments for data collection. Data on solid waste generation and the socioeconomic attributes of residents from 400 households were collected from residential zones within Bauchi town, the study area. Descriptive statistics, Correlations and Standard Multiple Regressions (SMR) were computed for data analysis using SPSS 2.2 software. Twelve (12) socioeconomic factors were computed in SMR to determine the significant factors of MSWG in the study. The results showed that five factors, namely: household size, income, education, house head age and occupation have exerted significant influence on MSWG in the study area. The results also showed that F (5:362) = 84.058 at p ≤ 0.01 and adjusted R² = 0.531; which indicated that the factors in the SMR model have sufficiently explained the variance in MSWG in Bauchi town. The study concluded that the five significant predictor factors have adequately explained the variance of MSWG in the study area. Therefore, the factors have implications for planning of effective waste management system in Bauchi town, Nigeria.